Study of the journalistic work of Wenceslao Fernández Flórez in his first stage. The influence in his literary work - Román Portas, Mercedes; Longueira Moris, Alicia (Estudios sobre el Mensaje Periodístico, 2013)
The works of the Galician writer Wenceslao Fernández Flórez (18851964) are relevant actually for their contents, but exists today some absences of knowledge about it. Their analysis allow us to state a strong connection among his personal experience, the critical commentary in press and, later, the literary description from his novels. We focus this study in three aspects that we consider a good example of his worries. The principal value of this investigation is that we can access to the personal file of the writer in the Foundation Wenceslao Fernández Flórez. This has allowed us to accede to unpublished documents, as his particular correspondence and diverse manuscripts.
Keywords: literature; journalism; woman; war; emigration.